Penerapan Rendam Kaki Air Hangat terhadap Tekanan Darah pada Lansia dengan Hipertensi: The Application of Warm Water Foot Soaking on Blood Pressure in Elderly with Hypertension - Aldy Mandaty, Fhandy; Syaifudin, Achmad; Sumarno, Sumarno; komsiyah, komsiyah; Nur Kumlasari, Dian; Handayaningtyas, Dita (Jurnal Keperawatan Berbudaya Sehat, 2025)
The elderly undergo a degenerative process that affects various bodily organ functions, including the cardiovascular system. One common disorder that occurs in this system is hypertension. Hypertension is a cardiovascular disease that cannot be completely cured, but it can still be controlled through proper management. Uncontrolled hypertension can lead to more serious health problems. The research aims to determine the application of warm foot soaks on blood pressure in elderly hypertensive individuals. The type of research is a case study with 4 research subjects, namely elderly patients suffering from hypertension. This research was conducted at one of the public health centers in Semarang City. The warm foot soak was performed for 15 minutes. Blood pressure measurements were taken twice, before and after the intervention. Warm foot soak therapy has been proven effective in lowering blood pressure in elderly hypertensive individuals, with an average reduction of  9 mmHg in systolic and 4 mmHg in diastolic pressure. It is hoped that classical music therapy will begin to be integrated as part of non-pharmacological interventions in the management of hypertension, particularly in the elderly.